1996
DOI: 10.1016/s0006-3495(96)79475-4
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally silent transitions in the bacteriorhodopsin photocycle

Abstract: The photocycle kinetics of bacteriorhodopsin were analyzed from 0 to 40 degrees C at 101 wavelengths (330-730 nm). The data can be satisfactorily approximated by eight exponents. The slowest component (half-time 20 ms at 20 degrees C) belongs to the 13-cis cycle. The residual seven exponentials that are sufficient to describe the all-trans photocycle indicate that at least seven intermediates of the all-trans cycle must exist, although only five spectrally distinct species (K, L, M, N, and O) have been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
229
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(257 citation statements)
references
References 27 publications
27
229
1
Order By: Relevance
“…The contributions of the photocycle intermediates to the b-spectra in (32). The rest (70%) should be due to N. This spectrum is identical to that obtained by exchanging the order of the last two time constants (k 5 and k 6 , in our case) as proposed by Chizhov et al (43), and similar to the penultimate spectrum shown in Figure 3A of Rödig et al (28). Spectrum b 6 (h) is roughly similar to b 5 (f) in shape, but with only one sixth the amplitude.…”
Section: Contribution Of L M N and O To The B-spectrasupporting
confidence: 89%
See 1 more Smart Citation
“…The contributions of the photocycle intermediates to the b-spectra in (32). The rest (70%) should be due to N. This spectrum is identical to that obtained by exchanging the order of the last two time constants (k 5 and k 6 , in our case) as proposed by Chizhov et al (43), and similar to the penultimate spectrum shown in Figure 3A of Rödig et al (28). Spectrum b 6 (h) is roughly similar to b 5 (f) in shape, but with only one sixth the amplitude.…”
Section: Contribution Of L M N and O To The B-spectrasupporting
confidence: 89%
“…The spectra obtained in this way, together with the rate constants, were then used to calculate the spectra for a reaction consisting of a linear sequence of intermediates, using the method of Chizhov et al (43).…”
Section: Spectra Of Model Intermediates (B-spectra)mentioning
confidence: 99%
“…Table 2 shows the presence of 6 kinetically distinct species with taus near 0.008, 0.05, 0.15, 0.5, 1.9, and 4.9 ms. These are essentially the same components as obtained previously by Hendler et al [14,20] and Chizhov et al [21] using optical data, and by Rodig et al [22] and Morgan et al [23 ] using FTIR data, and by Müller et al using both optical and FTIR data [24]. It is also shown in Table 2 that the component seen optically with a tau near 1.9 ms is absent in the electrical data.…”
Section: Discussionsupporting
confidence: 86%
“…Transitions among distinct structural states, each characterized by both structural order and internal dynamic disorder, are typically required for the function of a protein, especially an enzyme. To describe the mechanism of a protein's function is to describe its structural kinetics, i.e., the coupling of protein structural transitions to biochemical kinetics, as defined by changes in bound ligand (1)(2)(3). However, for most proteins there remains mechanistic ambiguity due to a gap between structural data, determined primarily from static protein crystals, and kinetics, measured during the transient phase of the biochemical reaction.…”
mentioning
confidence: 99%
“…All these data suggest This article is a PNAS Direct Submission. 1 To whom correspondence may be addressed. Email: yuri.nesmelov@uncc.edu or ddt@ umn.edu.…”
mentioning
confidence: 99%